2017
DOI: 10.1136/jclinpath-2015-203587
|View full text |Cite
|
Sign up to set email alerts
|

Clinical associations of the positive anti Ro52 without Ro60 autoantibodies: undifferentiated connective tissue diseases

Abstract: AimsAutoantibodies targeting Ro52 and Ro60 antigens are historically reported as anti SSA/Ro. In general anti SSA/Ro results are either anti Ro52+Ro60+ or anti Ro52−Ro60+ antibodies. Anti Ro52 without anti Ro60 (Ro52+ Ro60−) antibodies are often not reported routinely. This study intends to review the potential significance of these autoantibodies in the management of connective tissue diseases.MethodA ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 39 publications
2
19
0
5
Order By: Relevance
“…Finally, our study is probably the first to report on MS the presence of anti-Ro52 abs, an autoab marker of prototype autoimmune rheumatic diseases such as systemic lupus erythematosus and Sjögren's syndrome. This autoab, which is relatively frequent and can be found in non-autoimmune rheumatic diseases, as monospecificity (anti-Ro52 ab positive in the absence of anti-Ro60/SSA ) [38][39][40][41][42] is only present in 2 (1.5%) MS patients, a prevalence unexpectedly low, given the reported high prevalence of ANA in MS, autoimmune nature of the disease, and the relatively high prevalence of anti-Ro52 abs in the general population; all three points raising the logical expectation of a higher percentage rate for this autoab specificity in MS. None of these two patients had concomitant anti-Ro60/SSA abs or clinical evidence of Sicca syndrome.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, our study is probably the first to report on MS the presence of anti-Ro52 abs, an autoab marker of prototype autoimmune rheumatic diseases such as systemic lupus erythematosus and Sjögren's syndrome. This autoab, which is relatively frequent and can be found in non-autoimmune rheumatic diseases, as monospecificity (anti-Ro52 ab positive in the absence of anti-Ro60/SSA ) [38][39][40][41][42] is only present in 2 (1.5%) MS patients, a prevalence unexpectedly low, given the reported high prevalence of ANA in MS, autoimmune nature of the disease, and the relatively high prevalence of anti-Ro52 abs in the general population; all three points raising the logical expectation of a higher percentage rate for this autoab specificity in MS. None of these two patients had concomitant anti-Ro60/SSA abs or clinical evidence of Sicca syndrome.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, our study is probably the first to report on MS the presence of anti-Ro52 abs, an autoantibody marker of prototype autoimmune rheumatic diseases such as systemic lupus erythematosus and Sjögren's syndrome. This autoantibodies, which is relatively frequent and can be found in non-autoimmune rheumatic diseases, as monospecificity (anti-Ro52 antibody positive in the absence of anti-Ro60) [38][39][40][41][42] as only present in 2 (1.5%) MS patients, a prevalence unexpectedly low, given the reported high prevalence of ANA in MS, autoimmune nature of the disease, and the relatively high prevalence of anti-Ro52 abs in the general population; all three points raising the logical expectation of a higher percentage rate for this autoantibody's specificity in MS. None of these two patients had concomitant anti-Ro60 abs or clinical evidence of sicca syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, analysis of the involvement of anti‐PL‐7 and anti‐Jo‐1 autoantibodies in ILD may contribute to understanding the morbidity and severity of many PEP08‐negative patients. It was recently reported that the production of Ro52‐autoAbs in patient sera were related to undifferentiated connective tissue diseases (UCTD) . Measurement of PEP08‐Ab in sera of UCTD patients may contribute to the prediction of ILD.…”
Section: Discussionmentioning
confidence: 99%